International trade, crowding out, and market structure: Cournot approach - James P. Gander (The University of Utah, Department of Economics, 2017)
Using traditional Cournot demand concepts, the effect of an increase in export demand on the price and domestic quantity demanded for a given product under different market structures and production cost structures is examined. In general, an increase in the product price will result in a reduction in the domestic quantity demanded. This is the case of 'Crowding Out' (CO), analogous to that found in macroeconomics loanable funds analysis. An explicit algebraic simple model is developed for different cost structures; for which is derived several indexes of 'CO'. These indexes will reflect the different market structures by 'n', the number of firms in the industry. With these indexes, different export trade sceneries are demonstrated and discussed. One significant result is that for the decreasing cost case, there is the opposite effect, 'Crowding In'. Some implications of 'CO' for international trade policy are discussed briefly.
Keywords: 330; International Trade; Exports; Imports; "Crowding Out"; Market Structures; Cost Structures